PELATIHAN UMKM RUMAHAN INDUSTRI PANGAN SEBAGAI UPAYA MEMINIMALKAN KENDALA BERWIRAUSAHA DI DESA CIPEUNDEUY - Pramadista Sudrajat, Angga; Engkus; Anggara, Ruli (PT. ABIG RIZKY PUBLISHER, 2025)
The UMKM (Micro, Small, and Medium Enterprises) training on Home-Based Food Industry in Cipeundeuy Village is a capacity-building program aimed at minimizing various challenges faced by small business actors in pursuing entrepreneurship. The training focused on enhancing participants' knowledge and skills in business management, food product innovation, packaging techniques, and digital marketing. The methods applied combined theoretical sessions and hands-on practice. The results indicated a significant improvement in participants' understanding of basic entrepreneurial concepts and their ability to produce and market food products more professionally. The program also encouraged the formation of business groups and follow-up plans for continuous mentoring. Therefore, this training has proven to be an effective strategy in strengthening the rural food MSME sector